Outcome of Locally Advanced Esophageal Cancer Patients Treated With Perioperative Chemotherapy and Chemoradiotherapy Followed by Surgery. (January 2021) - Ahmed, Naseer; Owen, Justin; Abdalmassih, Michael; Khan, Junaid; Nugent, Zoann; Qing, Gefei; Martineau, Patrick; Rathod, Shrinivas; Dubey, Arbind; Bashir, Bashir; Chowdhury, Amitava; Buduhan, Gordon
Abstract : Objectives: Perioperative chemotherapy (P-CT) or neoadjuvant chemoradiation (C-RT) followed by surgical resection is the standard of care for locally advanced esophageal cancer (LAEC). We present an institutional review and outcome of patients with LAEC treated with neoadjuvant C-RT or P-CT followed by surgery. Methods: Patients were identified through the Manitoba Cancer Registry. Overall survival (OS), recurrence-free survival (RFS), and time to recurrence (TTR) were compared using proportion hazard regression analysis. Metabolic and pathologic response rates were compared by the Fisher exact test. Results: Sixty-seven patients were treated with C-RT and 32 with P-CT. Fifty-two percent of the patients had pretreatment and posttreatment positron emission tomography scans before surgery. Ninety-five percent of the patients in C-RT and 91% in P-CT had a partial metabolic response or stable disease. Sixty-one percent of C-RT and 34% of P-CT patients had tumor regression grade (TRG) 0 to 1; 39% of C-RT and 66% of P-CT had TRG 2 to 3 ( P =0.018). Median OS was 37 and 18 months for patients with TRG 0 to 1 and 2 to 3, respectively ( P =0.013, hazard ratio [HR]=1.96). Three-year OS was 43% versus 37% ( P =0.37, HR=1.30), RFS was 34% versus 26% ( P =0.87, HR=0.96), and median TTR was 30 versus 13 months ( P =0.07, HR=0.59) for C-RT and P-CT, respectively. Conclusions: C-RT was associated with a higher degree of pathologically tumor regression. Patients with major tumor regression had a better outcome than those with minimal to poor response. There was a trend toward improved TTR with C-RT but no difference in OS or RFS.